Analisis Perbandingan Penilaian Kualitatif Dan Kuantitatif Pada Pembelajaran Bahasa Sunda Di SDN Saparako - Aisah, Deuis; Irawan, Irawan; Sapdi, Rohmat Mulyana (JURNAL MANAJEMEN PENDIDIKAN, 2025)
Comparative Analysis of Qualitative and Quantitative Assessment in Sundanese Language Learning at Saparako State Elementary School Sundanese language learning in elementary schools plays a crucial role in preserving local cultural identity and shaping students’ character. However, assessment practices still reveal an imbalance between qualitative and quantitative approaches used by teachers. This study aims to compare both assessment types to identify their alignment, differences, and implications for accuracy and fairness within the context of the Merdeka Curriculum. Employing a descriptive-comparative design, the study analyzes qualitative assessments (narrative descriptions) and quantitative assessments (numerical scores) in Sundanese language in SDN Saparako. Findings indicate a strong positive correlation between the two approaches, although each reflects different dimensions of students’ abilities. Qualitative assessment captures learning processes, attitudes, and language performance, while quantitative assessment focuses on measurable learning outcomes. These results highlight the need to integrate both approaches to obtain a more comprehensive evaluation of students’ competencies. The study recommends developing an integrated mixed assessment model that aligns with local cultural values and supports holistic assessment principles promoted in the Merdeka Curriculum.